2001
DOI: 10.1128/aac.45.3.857-869.2001
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity and Pharmacokinetics of Posaconazole (SCH 56592) in Treatment and Prevention of Experimental Invasive Pulmonary Aspergillosis: Correlation with Galactomannan Antigenemia

Abstract: The antifungal efficacy, safety, and pharmacokinetics of posaconazole (SCH 56592) (POC) were investigated in treatment and prophylaxis of primary pulmonary aspergillosis due to Aspergillus fumigatus in persistently neutropenic rabbits. Antifungal therapy consisted of POC at 2, 6, and 20 mg/kg of body weight per os; itraconazole (ITC) at 2, 6, and 20 mg/kg per os; or amphotericin B (AMB) at 1 mg/kg intravenously. Rabbits treated with POC showed a significant improvement in survival and significant reductions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(128 citation statements)
references
References 49 publications
12
113
0
3
Order By: Relevance
“…10 However, studies have shown that orally administered posaconazole can achieve plasma concentrations that exceed the minimum inhibitory concentration for Aspergillus. 29,30 In addition, Krishna et al 31 have shown that oral posaconazole in allogeneic stem cell transplant patients with graft-versus-host disease achieves efficacious plasma concentrations and is not affected by variables such as body weight or grade of graftversus-host disease. In the patient population evaluated in this study, almost half of whom underwent stem cell transplant, with the majority of those having graft-versus-host disease, posaconazole was not expected to demonstrate superiority in terms of response and survival to parenteral antifungal therapy.…”
Section: Therapy Of Aspergillosis In Cancer Patientsmentioning
confidence: 99%
“…10 However, studies have shown that orally administered posaconazole can achieve plasma concentrations that exceed the minimum inhibitory concentration for Aspergillus. 29,30 In addition, Krishna et al 31 have shown that oral posaconazole in allogeneic stem cell transplant patients with graft-versus-host disease achieves efficacious plasma concentrations and is not affected by variables such as body weight or grade of graftversus-host disease. In the patient population evaluated in this study, almost half of whom underwent stem cell transplant, with the majority of those having graft-versus-host disease, posaconazole was not expected to demonstrate superiority in terms of response and survival to parenteral antifungal therapy.…”
Section: Therapy Of Aspergillosis In Cancer Patientsmentioning
confidence: 99%
“…Most rodent models of invasive aspergillosis require immunosuppression to produce consistent disease [12,17,20,25,26]. Immunocompetent mice can be infected by the i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Most instances are external breaks associated with mechanical or chemical stress (1)(2)(3). Internal breaks are relatively uncommon, but they can be caused by product defects, accidental needle-stick injury, the catheter becoming brittle with aging, and the intrinsic properties of polyurethane (4)(5)(6)(7)(8). In particular, it has been widely accepted that polyurethane catheters are highly biocompatible, but vulnerable to various types of physical and chemical stress that lead to polyurethane degradation (7,8).…”
Section: Editormentioning
confidence: 99%
“…In 2003, the US Food and Drug Administration approved the use of a double-sandwich GM enzyme immunoassay (Platelia Aspergillus EIA: Bio-Rad Laboratories) for the diagnosis of invasive aspergillosis in adult patients (7). The double-sandwich ELISA for detection of GM is reported to have high sensitivity and high specify for invasive aspergillosis when a cut-off value of 0.8 ng/mL is used (8).…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation